The protective and antiapoptotic effects of Hypericum triquetrifolium Turra against cyclophosphamide-induced lung injury in rats: in vitro evaluation - Çetik Yıldız, Songül; Keskin, Cumali; Şahintürk, Varol; Ayhancı, Adnan (The European Research Journal, 2024)
Objectives: Hypericum triquetrifolium Turra (HTT) has been traditionally used in medical treatments due to its sedative, antiseptic, antiinflammatory, and anthelmintic properties. The present study aims to investigate the lung-protective and antiapoptotic effects of HTT against cyclophosphamide (CP)-induced lung injury in rats. Methods: Thirty-five Sprague Dawley rats were categorized into 5 groups, each consisting of seven members. Phenolic acid and flavonoid contents of this plant were determined. The lung tissue samples cultivated from the rats were examined in histopathological and immunohistochemically for the apoptosis markers of Caspase-3, Bax, and Bcl-2. Results: Histopathological results indicated that structural defects, bleeding areas, and edema had occurred in the lungs of the CP-Alone Group. Besides, Caspase-3 and Bax positivity of the lung cells had also increased while Bcl-2 positivity had decreased. On the other hand, in the HTT+CP Group, HTT was shown to have reversed the aforementioned changes positively. Conclusion: Based on in vivo results, HTT could be a strong protective candidate for CP-induced lung injury and apoptosis